THE RELATIONSHIP BETWEEN STUDENTS’ LEARNING STYLES AND THEIR ACADEMIC ACHIEVEMENT - Rissa Dona Rizqi; Kurniawan Yudhi Nugroho (Proceedings Education and Language International Conference, 2017)
A descriptive study on students’ assumption about the relationship between learning styles and academic achievement. The aim of this study was to find out whether there is a relationship between learning styles and academic achievement. The writer used total sampling technique in collecting the data and questionnaire as the instrument of the study. The questionnaire was distributed to the sample that is all of the college of languages students of a Private University Semarang that are 62 students divided into two majors; education and literature programs. The writer tabulated the data using Microsoft excel and SPSS v.23.0 in order to know the results statistically. The results showed that the learning styles aspects had a relationship on the students’ academic achievement. It is proven by the statistical data of questionnaire’s Likert scale that most of the respondents give the response in scale of “4” which means the respondents agree with the statements on the questionnaire about the relationship between learning styles and academic achievement.Keywords: learning styles, academic achievement, students